2016
DOI: 10.1016/j.jmps.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

From yield to fracture, failure initiation captured by molecular simulation

Abstract: International audienceWhile failure of cracked bodies with strong stress concentrations is described by an energy criterion (fracture mechanics), failure of flawless bodies with uniform stresses is captured by a criterion on stress (yielding). In-between those two cases, the problem of failure initiation from flaws that moderately concentrate stresses is debated. In this paper, we propose an investigation of the process of failure initiation at the atomic scale by means of molecular simulations. We first discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…Yin et al [163] found that a local bond strength failure criterion seems to perform better than the Griffith criterion for a graphene sheet containing a crack shorter than 10 nm. Brochard et al [164] found a transition from energy-governed (Griffith criterion) to stress-governed failure in graphene, and proposed a composite failure criterion including both stress and energy.…”
Section: Strength and Toughnessmentioning
confidence: 99%
“…Yin et al [163] found that a local bond strength failure criterion seems to perform better than the Griffith criterion for a graphene sheet containing a crack shorter than 10 nm. Brochard et al [164] found a transition from energy-governed (Griffith criterion) to stress-governed failure in graphene, and proposed a composite failure criterion including both stress and energy.…”
Section: Strength and Toughnessmentioning
confidence: 99%
“…All simulations are performed with LAMMPS (http://lammps.sandia.gov, [8]). See [9][10][11] for more details regarding the set up of the molecular simulations.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…This non-linear behaviour may be due to factors such as: stress, energy release, non-linear deformations prior fracture and the phonon and atomic bonds instabilities. [25][26][27]…”
Section: Failure Responsementioning
confidence: 99%